PEMIMPIN AKADEMIK ATAU MANAJERIAL? Aspirasi, Harapan dan Tantangan Perempuan untuk Menjadi Pemimpin di Lembaga Pendidikan Tinggi Islam - Hidayah, Siti Nur; Munastiwi, Erni (PALASTREN: Jurnal Studi Gender, 2019)
The disparity of women leadership in higher education has been the concern of scholars for decades. However, the problem still exists until today. In the context of Islamic higher education in Indonesia, similar problem also continues to occur, yet the aspiration of young women lecturers has not been examined. This research aims to investigate the aspiration, hope, and challenges of young women lecturers at Islamic University in Banda Aceh, Indonesia on leadership positions. Employing in-depth interviews with 12 women lecturers in junior and mid leadership career this study found that: first,  women lecturers are less represented both in academic and managerial leaderships; second, all participants aspire more for academic leadership than the managerial one. However they would accept leadership position if they are given trust (amanah) or are appointed for that position; third,  the university uses a direct appointment model in the managerial positions, thus limiting highly motivated women or even men to apply for leadership career; and fourth, women academics have to deal with triple challenges in leadership careers: related to balancing between career and family as well as organizational culture and policies.